O movimento de software livre e a produção colaborativa do conhecimento - Sanches, Wilken David (2007)
This dissertation approaches the construction of a collaborative model of knowledge production disseminated by the Free Software Movement and its opposition to the current law of intelectual property. It describes the genesis of the free software movement as well as how it has become consolidated as an independent domain of knowledge production. In order to better illustrate the model of production proposed by the Free Software Movement and its virtual communities, this paper presents an analysis on the Debian project´s organization and structure for the making of decisions. It explores the limitations of the current model of intelectual property and how it has become a powerful tool for making knowledge a prisoner of private institutions. At last, this dissertation presents how this new model of collaborative production surpasses the software development and begins to influence different areas of knowledge, leaving behing the idea of intelectual property and becoming a concept of intelectual inheritance